INTUICJA W UCZENIU SIĘ JĘZYKÓW OBCYCH - Piegzik, Wioletta (Neofilolog, 2018)
The aim of this article is to present what the intuition is that occurs during communicative practice and gives us the immediate answer to different doubts and the immediate understanding of language structures without conscious reasoning and loading of the cognitive system. In the first part, we analyze different concepts of language intuition presented in lingusitic and foreign language acquisition. In the second part, a comparative analysis of automatic, controlled and intuitive processes is provided. We show that the distinction between operations that are automatic and those that are under control is a simplification and reduces the issue of foreign language acquisition. In the same part, we also argue for the use of intuition and suggest some indications favorable to implementation of this mental disposition.